2015
DOI: 10.1902/jop.2015.150287
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Soft Tissue Alterations and Esthetic Outcomes Following Immediate Implant Placement and Restoration of Single Implants in the Anterior Maxilla

Abstract: The IPR protocol resulted in generally acceptable soft tissue and esthetic outcomes, with suboptimal results reported in ≈11% of low-risk cases. Factors such as preoperative tissue biotype or use of a flap or connective tissue graft did not significantly influence soft tissue and esthetic outcomes. Long-term prospective controlled clinical trials are necessary to identify factors that may influence the esthetic outcomes associated with IPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
86
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 37 publications
11
86
0
1
Order By: Relevance
“…They found only four prospective studies reporting the frequency of advanced midfacial recession (> 1 mm), with a risk of less than 10% when an intact facial bone wall and thick gingival biotype were present and flapless surgery with immediate placement of a prosthetic crown were carried out. Similar results were found by Khzam et al in a recent systematic review in which advanced mucosal recession was seen in approximately 11% of low‐risk cases. The aim of the present review is to analyze factors affecting the position and stability of the peri‐implant soft‐tissue margin and to describe the surgical and combined prosthetic‐surgical approaches to treat unesthetic peri‐implant soft‐tissue dehiscence.…”
supporting
confidence: 89%
“…They found only four prospective studies reporting the frequency of advanced midfacial recession (> 1 mm), with a risk of less than 10% when an intact facial bone wall and thick gingival biotype were present and flapless surgery with immediate placement of a prosthetic crown were carried out. Similar results were found by Khzam et al in a recent systematic review in which advanced mucosal recession was seen in approximately 11% of low‐risk cases. The aim of the present review is to analyze factors affecting the position and stability of the peri‐implant soft‐tissue margin and to describe the surgical and combined prosthetic‐surgical approaches to treat unesthetic peri‐implant soft‐tissue dehiscence.…”
supporting
confidence: 89%
“…The literature cites conflicting results for MFR around IIP, with some reporting similar recession for thick and thin biotypes 5 whereas others show significant recession for thin biotype 27 . Although a recent systematic review found non‐significant difference in recession regardless of biotype after IIP, results were based on pooled estimates only 14 . This review expands on previous studies 13 , 14 by analyzing data in a meta‐analysis format.…”
Section: Discussionmentioning
confidence: 95%
“…The main objective of these previous analyses was to evaluate survival and success of IIP 4 , 13 . Other studies evaluated soft tissue response according to immediate restoration rather than surgical variables 14 . Hence, the specific objectives of this systematic review and meta‐analyses are to analyze overall soft tissue changes around IIP and evaluate effects of different surgical factors on soft tissue levels.…”
mentioning
confidence: 99%
“…Despite the positive effect of all these techniques, it needs to be realized that an optimal esthetic result can only be reached in selected cases (Khzam et al. ) as the tissue changes cannot be completely prevented or compensated (Esposito et al. ; Chen & Buser ; Lin et al.…”
mentioning
confidence: 99%